Neuromuscular Adaptations and Enhancement of Physical Performance in Female Basketball Players After 8 Weeks of Plyometric Training - Cherni, Yosser; Hammami, Mehrez; Jelid, Mohamed Chedly; Aloui, Ghaith; Suzuki, Katsuhiko; Shephard, Roy J.; Chelly, Mohamed Souhaiel (Frontiers in Physiology, 2021)
Abstract The aim of this study was to examine the effects of an 8-week in-season plyometric training program on the physical performance and neuromuscular adaptations of female basketball players. Twenty-seven elite female basketball players (aged 21.0 ± 2.6 years) were assigned between an experimental group (n =15) who substituted a part of their usual training with biweekly plyometric training, and a control group (n = 12) who maintained their standard basketball training. Analyses of variance and co variance assessed changes in 10, 20 and 30 m sprint times, ability to change direction (T-test), jumping ability (squat jump (SJ) and countermovement jump (CMJ)) with electromyographic assessment of the vastus lateralis, vastus medialis, and rectus femoris muscles during jumping and the isokinetic strength of the knee muscles. After 8 weeks of the plyometric program the experimental group enhanced change of direction performance (Δ = -3.90%, d = 0.67) and a greater thigh cross sectional area (Δ = 9.89%, d = 0.95) relative to controls. Neural adaptations included significant improvements of EMG parameters for the vastus medialis muscle during Squat Jumping (Δ = 109.3%, d = 0.59). However, trends to improvements of sprinting times and jumping performances did not reach significance. In addition, there were no gains in the peak torque and average power of the quadriceps and hamstring muscles at either slow or moderate test speeds. We conclude that 8-weeks of plyometric training (72 to 126 jumps) was insufficient to improve variables associated with basketball performance in our subject-group. Further studies of female basketball players, extending the program period and increasing the intensity and speed of jumps is recommended in the search for more significant results.